Sistem Informasi Manajemen Keuangan pada PT. Hulu Balang Mandiri Menggunakan Framework Laravel - Bambang Hermanto; Machudor Yusman; Nagara . (Universitas Lampung, 2019)
The rapid development of technology forces us to learn and adapt, especially in the field of information technology. Information technology makes information spread very fast and accurate. This makes information technology a very important role in the company's growth for various sector, especially financial information. On the other side, manual work that related to numbers have very big risk of miscalculations from the employees (human error) and takes a relatively longer time. With the development of the Financial Management Web Based Information System, it is expected to help companies manage their financial reports and make decisions based on financial data.This research has successfully developed Financial Management Web Based Information System by implementing the Laravel framework. The conclusion of this research is the Financial Management Web Based Information System by implementing the Laravel Framework successfully built in accordance with the agreed design, proved by the results of the test as appropriate as had been expected.